Making value-chain risk visible: Extending ENCORE for systemic insights - Funke, Hjalmar; Wassénius, Emmy; Crona, Beatrice; Christiaen, Christophe (Stockholm University, 2025)
This dataset contains two files. PART I contains all supplementary materials for the study 'Making value-chain risk visible: Extending ENCORE for systemic insights', including relevant background information and further analyses. All supplementary tables and figures mentioned in the paper are presented and described in detail. PART II presents the analysis of all the value-chains included in the study and presents all underlying data. The team has assessed three value-chains and analyzed the pressures and dependencies on nature of each with three complementary measures.

Microsoft Excel, 2508
Keywords: Earth and Environmental Sciences; Biodiversity; Risk assessment; ENCORE; Systemic risk; Qualitative data; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap